When allergies have no name: is idiopathic anaphylaxis driven by co-factors? - Elkhalifa, Shuayb; Elbashir, Haggar; Abuzakouk, Mohamed (Frontiers in Allergy, 2024)
Idiopathic anaphylaxis (IA) is a severe allergic reaction without identifiable external triggers, presenting significant challenges in diagnosis and management. However, growing evidence suggests that many cases classified as idiopathic may actually be driven by cofactors such as exercise, hormonal fluctuations, medications, or hidden allergens. This mini-review explores the evolving understanding of IA, highlighting the role of these cofactors in triggering or amplifying anaphylactic reactions. It emphasizes how advances in diagnostic tools, including component-resolved diagnostics, are helping to identify previously undetected allergens, leading to more accurate diagnoses and reducing the prevalence of true idiopathic cases. As our knowledge of anaphylaxis and its underlying mechanisms deepens, the need for comprehensive evaluations that account for cofactor involvement becomes increasingly clear. Continued research in this area is essential to improve patient outcomes and better manage this complex condition.